Electrospun magnetic nanocellulose–polyethersulfone-conjugated aspergillus oryzae lipase for synthesis of ethyl valerate - Nurul Hidayah Hussin; Roswanira Abdul Wahab; Nursyafiqah Elias; Adikwu Gowon Jacob; Mohamad Hamdi Zainal-Abidin; Faizuan Abdullah; Nurul Jannah Sulaiman; Mailin Misson (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
A novel greener MNC/PES membrane was developed through an electrospinning technique for lipase immobilization to catalyze the synthesis of ethyl valerate (EV). In this study, the covalent immobilization of Aspergillus oryzae lipase (AOL) onto an electrospun nanofibrous membrane consisting of magnetic nanocellulose (MNC) and polyethersulfone (PES) to produce EV was statistically optimized. Raman spectroscopy, Fourier-transform infrared spectroscopy: attenuated total reflection, field emission scanning electron microscopy, energy dispersive X-ray spectroscopy, thermal gravimetric analysis (TGA), and differential thermal gravimetric (DTG) of MNC/PES-AOL demonstrated that AOL was successfully immobilized onto the fibers. The Taguchi design-assisted immobilization of AOL onto MNC/PES fibers identified that 1.10 mg/mL protein loading, 4 mL reaction volume, 250 rpm stirring rate, and 50 ◦C were optimal to yield 72.09% of EV in 24 h. The thermal stability of MNC/PES-AOL was improved by ≈20% over the free AOL, with reusability for up to five consecutive esterification cycles while demonstrating an exceptional half-life of 120 h. Briefly, the electrospun MNC/PES fibers that immobilized AOL showed promising applicability in yielding relatively good EV levels. This study suggests that using MNC as fillers in a PES to improve AOL activity and durability for a longer catalytic process could be a viable option.